2005
DOI: 10.1111/j.1365-2745.2005.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection for resistance to the allelopathic effects of invasive plants

Abstract: Summary1 Exotic plant invasions often cause high mortality in native populations and therefore have the potential to be a powerful selective force. 2 We found that surviving individuals from North American communities that have experienced extensive invasion by Centaurea maculosa have higher tolerances to the Eurasian invader than individuals from communities that did not experience invasion. 3 Some native species grown from the seed of individuals that survived Centaurea invasion were more resistant to the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
190
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(204 citation statements)
references
References 44 publications
9
190
5
Order By: Relevance
“…Our results demonstrate that anthropogenic fire has shaped adaptive traits in H. aromaticum populations, thus challenging the widespread assumption that native plant species from the Chilean matorral are not adapted to fire because of its historical absence as a natural disturbance (13,14). A recent study reported an increase in the species richness of native annuals in several matorral communities following fires (18), which suggests that fire adaptations might be rather common in matorral species.…”
Section: Discussionmentioning
confidence: 65%
“…Our results demonstrate that anthropogenic fire has shaped adaptive traits in H. aromaticum populations, thus challenging the widespread assumption that native plant species from the Chilean matorral are not adapted to fire because of its historical absence as a natural disturbance (13,14). A recent study reported an increase in the species richness of native annuals in several matorral communities following fires (18), which suggests that fire adaptations might be rather common in matorral species.…”
Section: Discussionmentioning
confidence: 65%
“…As A. petiolata can form dense patches in just a few generations (28), selection pressures may quickly switch to favor lower glucosinolate levels. The selective benefit of allelopathic traits may also decrease over time if native plants or soil microbes evolve resistance, and this resistance is great enough to render the allelochemical ineffective (29). Ultimately, confidently determining the primary mechanisms creating the patterns that we have observed will require experimental approaches.…”
Section: Figmentioning
confidence: 99%
“…Autotoxicity at high expression levels decreases the germination, growth and yielding ability of a plant (Ben-Hammouda et al 2002). Experimental examination of allelopathy can also vary with extraction approaches, techniques to isolate specific allelochemicals and the substrate used (Callaway et al 2005). However, the incorporation of these weeds in the soil might be proved effective to inhibit the seed germination of weeds but how to avoid these allelochemicals not to affect the seed germination of the crop is a question that needs to be addressed on scientific backgrounds.…”
Section: Germination Percentagementioning
confidence: 99%